2023
DOI: 10.3390/microorganisms11040849
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Goat-Milk-Derived Lactic Acid Bacteria with Bacteriocin-like Activity and Probiotic Potentials

Abstract: In the current study, we screened 46 isolates of lactic acid bacteria (LAB) derived from goat milk for bacteriocin producers that can inhibit common foodborne pathogens (Staphylococcus aureus, Listeria monocytogenes, and Bacillus cereus). The following three strains that showed antimicrobial activity against all indicators were identified: Enterococcus faecalis DH9003 and DH9012, and Lactococcus lactis DH9011. Their antimicrobial products exhibited typical bacteriocin characteristics, such as heat stability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…Therefore probiotics must be hemolysin-free (Kim et al, 2022;Rahmani et al, 2022). None of the isolates showed β-hemolysis after 24 h, which is consistent with the results of Baccouri et al (2019), Kanak et al (2023), Yang et al (2023), andRahmani et al (2022).…”
Section: Hemolytic Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore probiotics must be hemolysin-free (Kim et al, 2022;Rahmani et al, 2022). None of the isolates showed β-hemolysis after 24 h, which is consistent with the results of Baccouri et al (2019), Kanak et al (2023), Yang et al (2023), andRahmani et al (2022).…”
Section: Hemolytic Activitysupporting
confidence: 87%
“…However, the present study demonstrated that the percentage of co-aggregation of all isolates with Gram-positive pathogen (L. monocytogenes) was significantly higher than with Gramnegative pathogen (E. coli). Results of previous studies did not show a relationship between the percentage of co-aggregation and Gram stain of the pathogen (Nami et al, 2019;Pytka et al, 2022;Kanak et al, 2023;Yang et al, 2023). Research evidence has shown that the co-aggregation percentage is dependent only on incubation time, probiotics, and pathogen strain (Kanak et al, 2023).…”
Section: Isolatesmentioning
confidence: 80%
“…Therefore probiotics must be hemolysin-free (Kim et al, 2022;Rahmani et al, 2022). None of the isolates showed β-hemolysis after 24 h, which is consistent with the results of Baccouri et al (2019), Kanak et al (2023), Yang et al (2023), andRahmani et al (2022).…”
Section: Hemolytic Activitysupporting
confidence: 83%
“…However, the present study demonstrated that the percentage of co-aggregation of all isolates with Gram-positive pathogen (L. monocytogenes) was significantly higher than with Gramnegative pathogen (E. coli). Results of previous studies did not show a relationship between the percentage of co-aggregation and Gram stain of the pathogen (Nami et al, 2019;Pytka et al, 2022;Kanak et al, 2023;Yang et al, 2023). Research evidence has shown that the co-aggregation percentage is dependent only on incubation time, probiotics, and pathogen strain (Kanak et al, 2023).…”
Section: Isolatesmentioning
confidence: 93%
“…It was observed that, Pleurotus eryngii was the best option for scaling up procedures among the various exotic mushrooms tested, including Lentinula edodes, and the analytical results provided original knowledge on high-scale mushroom-production processes. The screening of probiotic bacteria from goat's milk [6]. The authors found that Microorganisms 2024, 12, 736 2 of 3 three of the isolated strains had an auto-aggregative phenotype and produced bacteriocins with good heat stability.…”
mentioning
confidence: 99%